2014
DOI: 10.1186/1743-8977-11-23
|View full text |Cite
|
Sign up to set email alerts
|

Role of metal oxide nanoparticles in histopathological changes observed in the lung of welders

Abstract: BackgroundAlthough major concerns exist regarding the potential consequences of human exposure to nanoparticles (NP), no human toxicological data is currently available. To address this issue, we took welders, who present various adverse respiratory outcomes, as a model population of occupational exposure to NP.The aim of this study was to evaluate if welding fume-issued NP could be responsible, at least partially, in the lung alterations observed in welders.MethodsA combination of imaging and material science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 54 publications
6
87
1
1
Order By: Relevance
“…However, these broad applications of CuO NPs increase human exposure and, thus, the potential risk related to their short-and long-term toxicity. Andujar et al [84] provided the first evidence of a link between human exposure to metal NPs and long-term pulmonary effects in occupationally exposed welders. However, human pulmonary toxicity or metal fume fever after inhalation exposure to CuO NPs has not been reported in the literature.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…However, these broad applications of CuO NPs increase human exposure and, thus, the potential risk related to their short-and long-term toxicity. Andujar et al [84] provided the first evidence of a link between human exposure to metal NPs and long-term pulmonary effects in occupationally exposed welders. However, human pulmonary toxicity or metal fume fever after inhalation exposure to CuO NPs has not been reported in the literature.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Similarly, it has been proven that welding, with similar local high temperature as in the operation of EDM, generates nanoparticles in high concentrations especially close to the sources (Lee et al, 2007;Pfefferkorn et al, 2010;Gomes et al, 2012;Gomes et al, 2014). However, health risks associated with EDM air pollution are not yet clearly understood (Andujar et al, 2014). Jose et al (2010) evaluated the aerosol exposure of DEDM and showed that the aerosol concentration at breathing zone of the operator was above the permissible limit for repairable particulates (5 mg/m 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…In situ studies performed by Andujar et al [55] showed that the chemical ingredient of metal-oxide nanoparticles detected in macrophages presented in the lung tissue of welders, workers commonly exposed to metal fumes, were mainly Fe, Cr and Mn. By analysing THP-1 macrophages (PMA-differentiated cells) in vitro the authors demonstrated that Fe 2 O 3 and alloyed metal oxide MnFe 2 O 4 nanoparticles induce mainly the secretion of pro-inflammatory cytokines TNF-a, IL-1b, CCL-2, CCL-3, CCL-4 and CXCL-9.…”
Section: Macrophage Activation By Metal-oxide Nanomaterialsmentioning
confidence: 99%